A differential role for human hippocampus in novelty and contextual processing: Implications for P300. (17th June 2019) - Fonken, Yvonne M.; Kam, Julia W. Y.; Knight, Robert T.
Abstract: The role of the hippocampus in P300 has long been debated. Here, we present a theoretical framework that elucidates hippocampal contributions to scalp P300 based on intracranial and lesion research combined with emerging evidence on the role of the hippocampus in rapid statistical learning, memory, and novelty processing. The P300 has been divided in two subcomponents: a fronto‐central P3a related to novelty and distractor processing, and a parietal P3b related to target detection. Interest in a role for hippocampus in scalp P300 was sparked by P3‐like ERPs measured intracranially in human hippocampus. Subsequent medial temporal lobe lesion studies show intact scalp P3b, indicating that the hippocampus is not critical for P3b. This contrasts with the scalp P3a, which was significantly diminished in human patients with lesions in the posterior hippocampus. This suggests a differential role for hippocampus in P3a and P3b. Our framework purports that the hippocampus plays a central role in distractor processing that leads to P3a generation in cortical regions. We also propose that the hippocampus is involved at the end of the cognitive episode for both P3a and P3b implementing contextual updating. P3‐like ERPs measured in hippocampus may reflect input signals from cortical regions implementing updates based on the outcome of cognitive processes underlying scalp P3, enabling a model update of the environment facilitated by the hippocampus. Overall, this framework proposes an active role for the hippocampus in novelty processing leading up to P3a generation, followed by contextual updating of the outcome of both scalp P3a and P3b. Abstract : The hippocampus contributes to multiple cognitive functions in addition to its well‐known role in memory. However, the role of the hippocampus in the cognitive P300 ERP has been largely overlooked. Here, we present a framework in which the hippocampus plays a differential role in two subprocesses of the P300: P3a and P3b. Evidence reveals that the hippocampus plays a functional role in novelty processing leading to cortical generation of P3a as well as contextual updating of the outcome of both P3a and P3b. Future research should consider functional contributions of hippocampus to P300 processes.